Cinema India : the art of Bollywood (2002)
[Dt.:] Die Website präsentiert einen Ausschnitt der indischen Fimindustrie mit einer Auswahl von Bollywood-Postern, die im Rahmen einer Ausstellung im Victoria and Albert Museum in London vom 16.6. bis 6.10.2002 zu sehen waren. Es werden Poster von verschiedenen Fim-Klassikern gezeigt, u. a. dem Oscar nominierten Film-Epos "Mother India". - [Engl.:] The exhibition brings together some of the most remarkable examples of Indian cinema art. From large-scale hoardings and posters, to photo cards, booklets and original film trailers, the exhibition will display landmark images and explore major themes which outline the stylistic and historic development of Indian cinema. Posters from many classic films are represented: the Oscar nominated epic Mother India; Sholay (with its distinctive and influential typography) and recent blockbusters such as Lagaan and K3G.